Perbandingan Sistem Pendidikan Kejuruan di Indonesia dan Jerman: Studi Deskriptif Kualitatif Berdasarkan Perspektif Wakasek Kesiswaan - Mochamad Dicky Yudhantaka; Zakiah Maulidi Putri; Asep Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2025)
This study aims to describe a comparative analysis of the vocational high school (SMK) education systems in Indonesia and Germany, as viewed from the perspective of the Vice Principal for Student Affairs at SMKN 1 Kedawung. The research adopts a qualitative approach using descriptive methods. Data were obtained through documentation and interviews with key informants, specifically the Vice Principal for Student Affairs at SMKN 1 Kedawung in Cirebon. Data collection techniques included document analysis and semi-structured interviews, while data analysis was conducted through the processes of data collection, reduction, presentation, and conclusion drawing. The findings indicate that the vocational education system in Germany is highly integrated and well-established, particularly when compared to those of other developed countries. The Dual System (Ausbildung) model implemented in Germany is globally recognized as a prestigious framework for vocational education and training. This system provides numerous advantages for students, including a curriculum that is continuously updated and aligned with industry demands, opportunities to gain practical work experience, improved career prospects with competitive remuneration, and direct learning within actual work environments. In contrast, the adoption of the Dual System model in Indonesia continues to face several challenges, particularly in terms of relevance, quality, and industry engagement. Nevertheless, efforts toward improvement and systemic reform are ongoing